Optimization of isolation parameters for starch extraction from Amaranthus paniculates (Rajgeera) using response surface methodology - Yadav, Pooja; Bosco, Dr. John Don (International Journal of Advanced Engineering Research and Science, 2021)
Amaranthus paniculates is a pseudo-cereal. It is a potential reservoir of starch and the properties of end-use product are dependent on the starch. As the major component in Amaranthus paniculates is starch it is very necessary to standardize the process for starch isolation for the maximum recovery of starch with minimal impurities. The study was aimed to improve the isolation parameters for the starch extraction using response surface methodology (RSM). The NaOH concentration (0.00 - 0.75 %), sieve mesh size (100 - 300) and steeping time (1 - 24 hrs) were taken as independent variables and starch yield (%), protein (%) and fat (%) were taken as optimizing responses. Quadratic model was used to evaluate the results. The process was optimized at 0.375 % of NaOH concentration, sieve of 300 mesh and steeping time of 24 hrs for the desired results i.e starch yield (39.91%), protein (0.87%) and fat (0.53%) with a desirability level of 1.00